THE EFFECTIVENESS OF THE IMPLEMENTATION OF SUPREME COURT REGULATION (PERMA) NUMBER 2 OF 2012 IN HANDLING MINOR THEFT CRIMES IN THE FORM OF PALM FRUIT LOOTING - Muhammad Pangadilan Ritonga; Syahrul Bakti Harahap (Jurnal Ilmu Hukum dan Keadilan, 2026)
This research aims to analyze the regulation of the element of negligence in the Criminal Code and Law Number 22 of 2009 on Road Traffic and Transportation, the application of the element of negligence in the evidentiary process in criminal court practice, the legal considerations of judges in Decision Number 1331/Pid.Sus/2025/PN Mdn, as well as the obstacles and solutions in proving the element of negligence in traffic accident cases resulting in death.The results of the study show that the element of negligence in traffic accident crimes has been clearly regulated through Article 359 of the Criminal Code and Article 310 paragraph (4) of Law Number 22 of 2009 as a special provision. The application of the element of negligence in judicial practice is carried out through comprehensive proof by linking the defendant’s conduct to the applicable standard of due care. In Decision Number 1331/Pid.Sus/2025/PN Mdn, the judge has systematically considered the facts revealed at trial and the evidence presented, thereby concluding that the element of negligence and the defendant’s criminal liability were fulfilled. The obstacles in proving the element of negligence include limitations in witnesses and technical evidence, which can be addressed through the optimization of technology, improvement in the quality of investigations, and the active role of judges during trial in order to achieve fair and just law enforcement